1983
DOI: 10.1093/sleep/6.4.326
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Analysis of Insomnia

Abstract: Summary: Data from three consecutive nights in the sleep laboratory and data from psychological questionnaires and interviews were cluster-analyzed. A total of 89 physician-referred insomniacs were included, together with 10 good sleepers. The goal was to develop a purely empirical classification scheme of insomnia and to compare it with the Association of Sleep Disorders Centers' current nosology, which is based on clinical experience. The categories of chronic psychophysiologic insomnia and of childhood-onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Nonetheless, they also reported no significant differences in the mean MSLT scores of their insomniac volunteers and normals. Two other recent reports (22,23), although based on patient populations, also found that chronic insomniacs classified as either Alb or A9b or (in 22) A5 did not seem to have significantly elevated MMPI scales. This would appear to support the statement by Zorick et al that "Although psychological evaluation is an important part of the workup of the patient with insomnia, overgeneralization from the psychological profiles of some patients with insomnia may lead to the erroneous conclusion that all people with the complaint of insomnia are psychologically distressed" (22).…”
Section: Discussionmentioning
confidence: 70%
“…Nonetheless, they also reported no significant differences in the mean MSLT scores of their insomniac volunteers and normals. Two other recent reports (22,23), although based on patient populations, also found that chronic insomniacs classified as either Alb or A9b or (in 22) A5 did not seem to have significantly elevated MMPI scales. This would appear to support the statement by Zorick et al that "Although psychological evaluation is an important part of the workup of the patient with insomnia, overgeneralization from the psychological profiles of some patients with insomnia may lead to the erroneous conclusion that all people with the complaint of insomnia are psychologically distressed" (22).…”
Section: Discussionmentioning
confidence: 70%
“…It has been observed that most of the people who report sleep complaints feel excessive daytime sleepiness, irritability, and stress (39). The male population is more exposed to such perils, and, indeed, the sleep disturbance that causes most daytime sleepiness is obstructive sleep apnea (40).…”
Section: Discussionmentioning
confidence: 99%
“…PLMS have been associated with complaints and objective markers of sleep disturbance in some studies but not in others (1,(5)(6)(7)(8)(9). Further, challenging the clinical significance of PLMS was a cluster analysis indicating that good sleepers had more leg movements during sleep than insomniacs (10), as well as unpublished data from our laboratory suggesting an inverse association between PLMS and mortality.…”
Section: P Eriodic Limb Movements During Sleep (Plms Ormentioning
confidence: 92%